Cinema and Development in West Africa : Film as a Vehicle for Liberation - Genova, James Eskridge (Book collections on Project MUSE., 2013)
This book shows how the film industry in Francophone West African countries played an important role in executing strategies of nation building during the transition from French rule to the early postcolonial period. The author sees the construction of African identities and economic development as the major themes in the political literature and cultural production of the time. Focusing on film both as industry and aesthetic genre, he demonstrates its unique place in economic development and provides a comprehensive history of filmmaking in the region during the transition from colonies to sovereign states.